Multivariable analysis of physicochemical and functional characterization of four Thai pigmented rice varieties - Tai, N. V.; Kunyanee, K.; Luangsakul, N. (My University, 2023)
Four Thai pigmented rice varieties as know as colored rice — two sources of Manpo red rice [Manpo A (Ounjai company), Manpo B (Thongmanee comapny)], Hommali (red), and Riceberry (purple) were investigated. Result showed the moisture, protein, fat, ash, carbohydrate, and amylose contents of the four types of varieties ranged from 8.62-10.39%, 7.88-9.05%, 1.87-2.90%, 1.67-1.78%, 76.32-79.52%, and 14.17-26.67%, respectively. Abundant fat and protein contents were found in Manpo A, while Manpo B had the highest amylose content. Riceberry and Manpo A varieties were found to have low amylose content. Therefore, the functional properties of the rice varieties were also different. Among the different varieties, Riceberry possessed low swelling power, OAI, and pasting properties; it also exhibited high levels of solubility, WAI, and antioxidant properties. Pearson’s correlation illustrated the relationships among the properties of the rice varieties, which revealed that antioxidant compounds could prohibit the gelatinization process. PCA and HCA separated the cultivars into two groups and showed that Riceberry demonstrated significant differences in characteristics from other varieties, which confirmed that the high content of antioxidants could remarkably lower the value of pasting parameters of rice paste. Finally, this study found that colored rice varieties have a high level of antioxidants, which indicates their potential use as nutraceutical foods. The unique characteristics of colored rice warrants further research to facilitate their utilization in appropriate food products to enhance health benefits.
Keywords: Colored variety; Functional; Multivariable analysis; Physicochemical; Rice